A 5‐year rotational grazing changes the botanical composition of sub‐alpine and alpine grasslands. Issue 4 (18th July 2018) - Perotti, Elisa; Probo, Massimiliano; Pittarello, Marco; Lonati, Michele; Lombardi, Giampiero
Abstract: Aim: The implementation of Grazing Management Plans (GMP), a specific policy and management tool, aimed at enhancing farm productivity while preserving plant diversity, soil and landscape. The GMP are based on rotational grazing systems (RGS) with animal stocking rate adjusted to balance grassland carrying capacity. The aim was to test the 5‐year effects produced by GMP implementation on botanical composition, plant diversity and soil nutrient content on sub‐alpine and alpine pastures. Location: Val Troncea Natural Park, western Italian Alps. Methods: A total of 199 vegetation transects was carried out in summer 2011 and repeated in summer 2016. The botanical composition was recorded and plant diversity indices, i.e. species richness and Shannon diversity ( H ′ index), were computed. Mean soil nutrient content was indirectly estimated through computation of Landolt N indicator value ( N index) for each transect. Pair‐sample statistical tests and PERMANOVA were perfomed at different levels: on the whole vegetation dataset, on vegetation communities (i.e. vegetation types and ecological groups) and considering functional pools of species. Results: Considering the whole vegetation dataset, species richness, H ′ index and N index significantly increased from 2011 to 2016. Moreover, species richness significantly increased in almost all vegetation ecological groups, with the highest increase within the mesotrophic group. The H ′ index significantly increased in eutrophic, pre‐forest and thermic groups, while the N index increased in all vegetation groups, except in the eutrophic and snow‐bed groups. A significant difference in botanical composition was detected within oligotrophic, mesotrophic and thermic groups. The number and cover of N‐poor high‐elevation species increased in all groups and this result might be related to effects produced by livestock, which promoted seed transport and increased connectivity amongst different communities. The meso‐eutrophic species number and cover significantly increased within thermic, mesotrophic and pre‐forest groups, suggesting greater use of such areas by livestock under RGS than under continuous grazing. Conclusions: The implementation of RGS with stocking rate adjustments proved to be an effective and a sustainable management tool to enhance botanical composition and plant diversity of sub‐alpine and alpine grasslands over a 5‐year span. Abstract : The implementation of a rotational grazing system with stocking rate adjustments proved to be an effective and a sustainable management tool to enhance botanical composition and plant diversity (species richness and Shannon diversity index) of sub‐alpine and alpine grasslands over a 5‐year span.